2010
DOI: 10.2486/indhealth.ms1139
|View full text |Cite
|
Sign up to set email alerts
|

Association between Workaholism and Sleep Problems among Hospital Nurses

Abstract: The present study examined the association between workaholism, the tendency to work excessively hard in a compulsive fashion, and sleep problems among Japanese nurses. A cross-sectional survey was conducted among 600 nurses from 2 university hospitals in Japan using a self-reported questionnaire on workaholism, sleep, job-related variables (i.e., job demands, job control, and worksite support), and demographic variables. A total of 394 nurses returned the questionnaire (response rate=65.7%) and complete data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 37 publications
6
80
0
2
Order By: Relevance
“…In one study, persons with the highest scores on workaholism were more likely than workers with low scores to report sleep problems, tiredness at work, and difficulties waking up in addition to fatigue in the mornings (Kubota et al, 2010). In the other study, Andreassen et al (2011) found that high obsessive work drive was associated with insomnia.…”
Section: Consequencesmentioning
confidence: 99%
“…In one study, persons with the highest scores on workaholism were more likely than workers with low scores to report sleep problems, tiredness at work, and difficulties waking up in addition to fatigue in the mornings (Kubota et al, 2010). In the other study, Andreassen et al (2011) found that high obsessive work drive was associated with insomnia.…”
Section: Consequencesmentioning
confidence: 99%
“…Workaholism, then, as a “negative addiction”, involves (a) excessive time spent working and, importantly, (b) difficulty disengaging from work, way beyond the call of the job, which often elicits negative emotions during and after a work episode; (c) frustration and agitation when prevented from working (e.g., when with family); (d) association with an inflexible or compulsive working style, leading potentially to poor relationships with others at work and at home [5,3740], though both enthusiastic workaholics and non-enthusiastic workaholics experience relatively high work-family conflict [41]; and (e) negative life outcomes including high perceived stress, low self-esteem, low life satisfaction, difficulties sleeping [24,4245], career dissatisfaction and poor performance [25,46], delay of planned retirement [47], work “burnout” [26,4852] and ill-health [11,14,21,47,53–56]. …”
Section: Workaholism As An Addiction With Negative Consequencesmentioning
confidence: 99%
“…As a result they become emotionally or cognitively exhausted over time (Taris, Schaufeli, & Verhoeven, 2005b). There are evidences that workaholic people suffer in diminished sleep quality (Kubota, Shimazu, Kawakami, Takahashi, Nakata, & Schaufeli, 2010), and worse psychological health (e.g., Burke, 2000;). …”
Section: Workaholism and Well-beingmentioning
confidence: 99%